1999
DOI: 10.1002/(sici)1097-0258(19990730)18:14<1803::aid-sim217>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Visit-driven endpoints in randomized HIV/AIDS clinical trials: impact of missing data on treatment difference measured on summary statistics

Abstract: In randomized HIV/AIDS clinical trials, CD4 lymphocyte counts and plasma HIV-1 RNA measurements are often used as endpoints. The comparison between treatment groups is mainly based on a summary measure of outcome, so-called summary statistic. Such analyses are often complicated by missing data occurring as drop-outs. For the most currently used summary statistics in these trials, we examined the impact of missing data occurring as drop-outs on test size, in order to help choosing between these statistics. A si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Slopes of changes over time, mean changes at week 72 and confidence intervals were estimated from the models, using all available data except baseline. Piecewise linear models (two phases) were proposed when the improvement in data fitting was significant [14,15]. According to the published studies [8], we explored three possible junction points: W8, W24 and W36.…”
Section: Methodsmentioning
confidence: 99%
“…Slopes of changes over time, mean changes at week 72 and confidence intervals were estimated from the models, using all available data except baseline. Piecewise linear models (two phases) were proposed when the improvement in data fitting was significant [14,15]. According to the published studies [8], we explored three possible junction points: W8, W24 and W36.…”
Section: Methodsmentioning
confidence: 99%
“…Although the last-observation-carried-forward method can overestimate the individual drug effect if the HIV-1 RNA level rebounds quickly after virologic failure, it was chosen to provide a consistent rule for handling patients in either group who discontinued treatment or had virologic failure, as well as for those who switched to enfuvirtide. 18,19 The robustness of the primary result was confirmed by three stringent sensitivity analyses that clearly showed that the magnitude of the estimate of the effect of enfuvirtide treatment was not determined primarily by the method of imputation.…”
Section: Updated Safety Analysismentioning
confidence: 85%
“…In practice, dropouts in the run-in period will carry a cost penalty and detailed comparisons might wish to take this into account. An algorithm was used to compute the necessary sample size for all possible designs involving up to five scans with scans potentially at baseline, 3,6,9,12,15,18,21,24,27,30,33 and 36 months. The 'optimal' design of a particular type is defined to be the one requiring the fewest subjects and this is presented assuming 10, 20 and 30 per cent annual dropout rates post-randomization.…”
Section: Optimal Designs With a Maximum Of 3 Years Follow-upmentioning
confidence: 99%
“…Hence, the rate of brain loss is a natural outcome measure to use in a randomized controlled clinical trial in AD. Other settings in which a rate of change is a natural outcome include applications in cardiovascular disease [2] and AIDS [3] or indeed any situation where a linearly divergent treatment effect might be anticipated [4].…”
Section: Introductionmentioning
confidence: 99%